Undergraduate Skill Programme (USK) - UMP, FSKKP (Faculty of Computer Systems and Software Engineering, 2011)
UMP established a Strategic Collaboration with Universitas Sumatera Utara (USU) and AMIK Tunas Bangsa, the two ways communication for Malaysia and Indonesia.